PENGGUNAAN METODE RESITASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK - Winyatul Hasanah (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2024)
The purpose of writing this journal is to find out the extent of improving student learning outcomes by using the recitation method in the subject of moral beliefs at MI Tarbiyatul Ikhwan. The research method used was a classroom action research method which was carried out in 2 cycles using the recitation method in grade 2 of MI Tarbiyatul Ikhwan. The data source was obtained from the 2nd grade as many as 19 students. The data collection technique in this study uses observation sheets. Data analysis uses quantitative calculations which are then described in the form of percentages. The results of the study show that the application of the recitation method can improve student learning outcomes in the subject of moral beliefs. Judging from observations with a total of 19 students. The students who obtained complete scores amounted to 8 people. Then it increased in cycle 1 by 12 people with a percentage of 63%. And increased in cycle 2 by 17 people with a percentage of 89%.